Structured design ... / [mikrofilem] - 320403 Camallil Omar; Halijah Ibrahim, 1970-; Maizan Baba, 1959-; Ngadiso Darus; Razali Ngah (Nottingham : University of Nottingham, 1997)
Thesis (Master of Science (Electronic Engineering)) - University of Nottingham, 1997